Aluminum alloy shoe tree with high wear resistance and heat-conducting property as well as efficient forming method and application of aluminum alloy shoe tree
By plating the Ag alloy transition layer and the CrZrCu alloy functional layer on the substrate of the aluminum alloy shoe last, the problems of low forming efficiency and short service life of the aluminum alloy shoe last are solved, and a shoe last with high precision, thermal conductivity and wear resistance are achieved.
Patent Information
- Application Number
- CN202411887269.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-01
AI Technical Summary
The current laser additive-made aluminum alloy shoe lasts have low forming efficiency, surface quality and dimensional accuracy cannot be guaranteed, and their service life needs to be improved.
AlSi10Mg aluminum alloy is used as the wire material, and the forming matrix is made by arc fuse additive, and under the protection of inert gas, the Ag alloy transition layer and CrZrCu alloy functional layer are plated on the surface of the matrix through DC magnetron sputtering to form an aluminum alloy shoe last with high wear resistance and thermal conductivity.
The high dimensional accuracy, high thermal conductivity and high wear resistance of aluminum alloy shoe lasts are achieved, metallurgical bonding is improved, the difference in thermal expansion coefficient between different materials is reduced, and the service life is extended.
Smart Images

Figure CN119736592A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of additive manufacturing, and specifically relates to an aluminum alloy shoe last with high wear resistance and thermal conductivity, and an efficient molding method and application thereof. Background Art
[0002] The shoe last is the molding mold of the shoe, which determines the basic shape of the shoe, including the curvature of the upper, the shape of the toe (such as pointed toe, round toe), the height and shape of the heel, and many other aspects. In the shoemaking industry, the shoe last provides a unified standard for mass production of shoes. High-quality shoe lasts are the prerequisite for manufacturing high-quality shoes.
[0003] At present, the main materials of shoe lasts are wood, polymers and metals. Compared with shoe lasts made of other materials, metal shoe lasts have many irreplaceable advantages, such as: (1) high compressive strength. When making shoes such as work shoes that need to withstand large external forces, they can better maintain the shoe shape, prevent deformation, and ensure the structural stability of the shoes during use; (2) good temperature resistance. When producing injection-molded shoes, molded shoes, vulcanized shoes and other shoes that require high temperature and high pressure processes, metal shoe lasts will not deform due to high temperatures, which can ensure the quality and dimensional accuracy of the finished shoes and meet the needs of large-scale industrial production; (3) high dimensional accuracy. Metal shoe lasts can be manufactured through precise processing technology, which can achieve high dimensional accuracy and ensure that the shape and size of each pair of shoes are highly consistent, which helps to improve production efficiency and product quality. It is especially suitable for the production of shoes with high dimensional accuracy requirements; (4) long service life. Metal materials are strong and durable, not easy to wear and crack, have a long service life, can be used repeatedly, reduce the frequency of replacement due to damage to the shoe last, and reduce production costs; (5) strong repairability. If a metal shoe last is partially damaged or deformed, its shape and performance can be restored through repair processes, while the repair of wood and plastic shoe lasts is relatively difficult.
[0004] Common manufacturing methods for metal shoe lasts include casting, forging, welding and additive manufacturing. Compared with other metal shoe last manufacturing methods, additive manufacturing can quickly produce complex shapes and structures without the need for traditional molds, shortening the production cycle and reducing costs. It is especially suitable for small-batch, personalized shoe last manufacturing. At present, the most commonly used method for manufacturing metal shoe lasts is selective laser melting (SLM), which has the characteristics of high forming accuracy and the ability to form complex structural parts. However, since metal shoe lasts are mostly made of aluminum alloy (good thermal conductivity, light weight and corrosion resistance, low cost), aluminum alloy has extremely high reflectivity to lasers, which leads to low energy utilization during the forming process of aluminum alloy shoe lasts, resulting in low forming efficiency, and high reflectivity makes it difficult to form a molten pool, resulting in poor forming quality. In addition, during the long-term use of shoe lasts, the insufficient wear resistance of aluminum alloy is also a problem that needs to be urgently solved in the industry. Although traditional surface strengthening methods (electroplating and thermal spraying, etc.) will improve the wear resistance of shoe lasts, they will reduce the overall thermal conductivity of aluminum alloy shoe lasts and thus affect shoemaking efficiency. The difference in thermal properties between the plated metal and the base metal will also lead to problems such as excessive stress and poor bonding stress, greatly shortening the service life of the coating. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problems of low forming efficiency, inability to guarantee surface quality and dimensional accuracy, and need to improve service life of the existing laser additive manufacturing method of aluminum alloy shoe lasts, and to provide an aluminum alloy shoe last with high wear resistance and thermal conductivity and its efficient forming method and application.
[0006] One of the purposes of the present invention is to provide an efficient forming method for an aluminum alloy shoe last having both high wear resistance and thermal conductivity, the method being carried out according to the following steps:
[0007] S1: 3D modeling of the shoe last, and then using AlSi10Mg aluminum alloy as wire to form the AlSi10Mg aluminum alloy shoe last matrix through arc fuse additive manufacturing;
[0008] S2: After finishing to high dimensional accuracy, pickling with phosphoric acid solution is used, and then, under the protection of inert gas, a Ag alloy transition layer is plated on the surface of the substrate by DC magnetron sputtering, and the composition and mass content of the Ag alloy are Ag: 82-84%, Zn: 12-14% and Sn: 4-5%;
[0009] S3: Under the protection of inert gas, a CrZrCu alloy functional layer is plated on the surface of the Ag alloy transition layer by DC magnetron sputtering. The composition and mass content of the CrZrCu alloy are Cu: 75-80%, Cr: 10-18%, Zr: 4-6%, Nb: 2-3% and Sn: 1-2%, thereby obtaining an aluminum alloy shoe last with both high wear resistance and thermal conductivity.
[0010] It is further defined that the wire diameter in S1 is 1.2-1.6 mm.
[0011] It is further defined that the arc fuse additive manufacturing process in S1 is: argon protection, CMT mode, wire feeding speed is 5-7m / min, current is 190-200A, voltage is 14-16V, and operating speed is 0.3-0.5m / min.
[0012] It is further defined that the concentration of the phosphoric acid solution in S2 is 10-30 wt %, the pickling temperature is 40-60° C., and the time is 5-15 min.
[0013] It is further defined that the magnetron sputtering process in S2 is as follows: the substrate temperature is 100-200°C, the working gas pressure is 0.3-1Pa, the bias voltage is -50 to -100V, and the Ag alloy target power is 50-150W.
[0014] It is further defined that the thickness of the Ag alloy transition layer in S2 is 0.2-0.9 μm.
[0015] It is further defined that the magnetron sputtering process in S3 is as follows: the substrate temperature is 200-300°C, the working gas pressure is 0.5-2Pa, the bias voltage is -100~-150V, and the CrZrCu alloy target power is 300-500W.
[0016] It is further defined that the thickness of the CrZrCu alloy functional layer in S3 is 2-3 μm.
[0017] A second object of the present invention is to provide an aluminum alloy shoe last made according to the above method.
[0018] The third object of the present invention is to provide an application of the aluminum alloy shoe last made by the above method in the shoemaking industry.
[0019] The advantages of the present invention compared to the prior art are:
[0020] (1) The present invention designs an Ag alloy specifically used for the AlSi10Mg aluminum alloy shoe last of the present invention as a transition layer. The Ag alloy has good thermal conductivity and wettability, and can react with the AlSi10Mg aluminum alloy to a certain extent to form a good metallurgical bond. In the design of the Ag alloy, Ag is used as a matrix material, and the content is maintained at 82-84% (mass fraction), providing good electrical conductivity, thermal conductivity and certain ductility; the Zn content is 12-14%, which can improve the thermal expansion coefficient of the alloy to a certain extent, reduce the difference in thermal expansion coefficient between the Ag alloy as the intermediate layer and the AlSi10Mg aluminum alloy layer, and can improve the strength and hardness of the alloy; the Sn content is 4-5%, which can not only further adjust the thermal expansion coefficient of the Ag alloy, but also enhance the corrosion resistance, and can also refine the grains, improve the wear resistance and fatigue resistance.
[0021] (2) The present invention designs a CrZrCu alloy specifically used in the present invention as a functional layer coating for AlSi10Mg aluminum alloy shoe lasts. The CrZrCu alloy reduces the difference between the traditional CrZrCu alloy and AlSi10Mg, reduces the stress of dissimilar materials caused by temperature changes during heating, and greatly improves the bonding strength. In the design process of the CrZrCu alloy of the present invention, Cu is used as the matrix material, and the content is maintained at 75-80% (mass fraction), which has good electrical conductivity and certain corrosion resistance, and its thermal expansion coefficient is relatively high, providing a basis for the basic properties of the alloy; the Cr content is 10-12%, which can form a dense oxide film on the surface to improve the corrosion resistance of the alloy. At the same time, it can also refine the grains and improve the strength and wear resistance of the alloy; Zr content is 4-6%, which can form stable compounds with copper, improve the strength and hardness of the alloy, and can improve the alloy's resistance to thermal fatigue, which helps to maintain stable performance in a temperature-changing environment; Nb content is 2-3%, which can form complex compounds with elements such as copper and chromium. These compounds play a role of dispersion strengthening in the alloy and improve the wear resistance of the alloy; Sn content is 1-2%, which can improve the corrosion resistance of the alloy, and can improve the processing performance of the alloy, making it easier to form into the desired shape.
[0022] (3) The AlSi10Mg aluminum alloy shoe last of the present invention uses the above-mentioned Ag alloy and CrZrCu alloy as the coating strengthening layer. The obtained shoe last has high dimensional accuracy, high thermal conductivity, and high wear resistance. The AlSi10Mg aluminum alloy matrix and the intermediate transition layer Ag alloy, and the Ag alloy and the CrZrCu alloy all have excellent metallurgical bonding, and the thermal expansion coefficients of the three present a gentle transition, which can effectively reduce the problems of reduced bonding strength and stress cracking caused by the large difference in thermal expansion coefficients between dissimilar materials under rapid temperature changes. The designed transition layer Ag alloy can form an excellent metallurgical bond with the matrix AlSi10Mg and the functional layer coating CrZrCu alloy, thereby improving the comprehensive performance of the AlSi10Mg aluminum alloy shoe last; the functional layer coating CrZrCu alloy can greatly improve the wear resistance and corrosion resistance of the AlSi10Mg aluminum alloy shoe last, and can long-term guarantee the dimensional accuracy, surface roughness and service life of the shoe last. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the cross-sectional morphology of the alloy material obtained in Comparative Example 1;
[0024] Figure 2 The cross-sectional morphology of the alloy material obtained in Example 1;
[0025] Figure 3 This is the transition result of the main elements in the alloy obtained in Example 1. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0028] Embodiment 1: The efficient forming method of the aluminum alloy shoe last with both high wear resistance and thermal conductivity of this embodiment is carried out according to the following steps:
[0029] (1) Computer-aided design (CAD) software was used to construct a three-dimensional model according to the size, shape, and style requirements of the shoe last. AlSi10Mg aluminum alloy wire with a diameter of 1.2 mm was used as the deposition material. Ar was used as the shielding gas with a gas flow rate of 20 L / min. The arc fuse additive manufacturing process parameters were shown in Table 1 to obtain the AlSi10Mg aluminum alloy shoe last substrate.
[0030] Table 1 Arc fuse additive manufacturing process parameters
[0031]
[0032] (2) The shoe last substrate was finely processed by a CNC machine tool, with a dimensional accuracy of ±0.2 mm and a surface roughness of Ra0.2. After fine processing, it was pickled with a phosphoric acid solution with a mass fraction of 20%, the pickling temperature was 50°C, and the pickling time was 10 minutes to remove the surface oxide film and improve surface activation. The pickled shoe last substrate was ultrasonically cleaned with ethanol and acetone for 20 minutes each, and dried in a drying oven at 60°C for 30 minutes.
[0033] (3) The shoe last substrate was placed in the vacuum chamber of the DC magnetron sputtering equipment. The sample stage speed was 20 r / min and the vacuum was evacuated to 1.3×10 -4 pa, the ion source cleans the sample surface, the Ar flow rate is 30sccm, and the time is 20min. Then, under Ar protection, the Ag alloy transition layer is plated, and the coating parameters are: substrate temperature is 160℃, working pressure is 0.6Pa, bias voltage is -70V, Ag alloy target power is 110W, film thickness is 0.46μm, and the Ag alloy target is closed. Among them, the composition and mass content of the Ag alloy are shown in Table 2. The thermal expansion coefficient of the Ag alloy is 20.4×10 -6 / K, thermal conductivity is 273.1W / m·K.
[0034] Table 2 Chemical composition of transition layer Ag alloy
[0035] element Ag Zn Sn Content (wt%) 84% 12% 4%
[0036] (4) After the transition layer Ag alloy is plated, the CrZrCu composite target is turned on to plate the CrZrCu alloy functional layer. The coating parameters are as follows: substrate temperature is 240°C, working pressure is 1.2 Pa, bias voltage is -130 V, CrZrCu target power is 380 W, and film thickness is 2.35 μm. The composition and mass content of the CrZrCu alloy are shown in Table 3. The thermal expansion coefficient of the CrZrCu alloy is 14.6×10 -6 / K, and the thermal conductivity is 333.6W / m·K to obtain an aluminum alloy shoe last with both high wear resistance and thermal conductivity.
[0037] Table 3 Chemical composition of functional layer coating CrZrCu alloy
[0038] element Cu Cr Zr Nb Sn Content (wt%) 80% 12% 4% 2% 2%
[0039] The thermal expansion coefficient and thermal conductivity of each part of the aluminum alloy shoe last are shown in Table 4.
[0040] Table 4 Thermal physical parameters of different areas of the shoe last in Example 1
[0041] structure Base material Transition layer material Functional layer coating materials Material AlSi10Mg Ag Alloy CrZrCu alloy <![CDATA[Coefficient of thermal expansion (10 -6 / K, 20 - 100 °C)]]> 22.1 20.4 14.6 Thermal conductivity (W / m·K) 172 273.1 333.6
[0042] As can be seen from Table 4, the present invention achieves a good gradient transition of thermal expansion among the base material, the transition layer material and the functional layer coating material through the design of the transition layer and the functional layer, so as to minimize the stress cracking and debonding problems caused by the difference in thermal properties of dissimilar materials.
[0043] Comparative Example 1:
[0044] The difference between this comparative example and Example 1 is that the Ag alloy composition used in step (2) is as shown in Table 5.
[0045] Table 5 Chemical composition of transition layer Ag alloy of comparative example 1
[0046] element Ag Zn Sn Content (wt%) 52% 32% 16%
[0047] The material sections of Example 1 and Comparative Example 1 were characterized, and their morphologies are shown in the following figure: Figure 1-2 As shown in the figure, it can be seen from the comparison that the thermal properties of the substrate, transition layer and functional layer of the comparative example material do not form a smooth transition, and obvious cracking and debonding occur between the three. However, the two interfaces between the substrate, transition layer and functional layer of the embodiment of the present invention form a good combination. The specific morphology is as follows: Figure 2 As shown, from Figure 3 The same results can be obtained for the main element transition results.
[0048] The surface hardness of the AlSi10Mg aluminum alloy shoe last before coating (AlSi10Mg aluminum alloy shoe last substrate) is 82HB. After being treated in Example 1, the surface hardness reaches 147HB, and the hardness is increased by 79%. At a shoe last working temperature of 100°C, the service life is increased by 3.9 times.
[0049] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. An efficient forming method of an aluminum alloy shoe last with high wear resistance and thermal conductivity, characterized in that: The method: S1: 3D modeling of the shoe last, and then using AlSi10Mg aluminum alloy as wire to form the AlSi10Mg aluminum alloy shoe last matrix through arc fuse additive manufacturing; S2: After finishing to high dimensional accuracy, pickling with phosphoric acid solution is used, and then, under the protection of inert gas, a Ag alloy transition layer is plated on the surface of the substrate by DC magnetron sputtering, and the composition and mass content of the Ag alloy are Ag: 82-84%, Zn: 12-14% and Sn: 4-5%; S3: Under the protection of inert gas, a CrZrCu alloy functional layer is plated on the surface of the Ag alloy transition layer by DC magnetron sputtering. The composition and mass content of the CrZrCu alloy are Cu: 75-80%, Cr: 10-18%, Zr: 4-6%, Nb: 2-3% and Sn: 1-2%, thereby obtaining an aluminum alloy shoe last with both high wear resistance and thermal conductivity.
2. The method according to claim 1, characterized in that The wire diameter in S1 is 1.2-1.6 mm.
3. The method according to claim 1, characterized in that S1 medium arc fuse additive manufacturing process: argon protection, CMT mode, wire feeding speed is 5-7m / min, current is 190-200A, voltage is 14-16V, and operating speed is 0.3-0.5m / min.
4. The method according to claim 1, characterized in that The concentration of phosphoric acid solution in S2 is 10-30wt%, the pickling temperature is 40-60°C, and the pickling time is 5-15min.
5. The method according to claim 1, characterized in that Magnetron sputtering process in S2: substrate temperature is 100-200℃, working gas pressure is 0.3-1Pa, bias voltage is -50~-100V, and Ag alloy target power is 50-150W.
6. The method according to claim 1, characterized in that The thickness of the Ag alloy transition layer in S2 is 0.2-0.9μm.
7. The method according to claim 1, characterized in that Magnetron sputtering process in S3: substrate temperature is 200-300℃, working gas pressure is 0.5-2Pa, bias voltage is -100~-150V, and CrZrCu alloy target power is 300-500W.
8. The method according to claim 1, characterized in that The thickness of the CrZrCu alloy functional layer in S3 is 2-3 μm.
9. Aluminum alloy shoe last made by the method according to any one of claims 1 to 8.
10. Application of the aluminum alloy shoe last made by the method according to any one of claims 1 to 8 in the writing industry.